COMPREHENSIVE ASSESSMENT OF THE USE OF PHOTOVOLTAIC STATIONS FOR POWERING PUMPS IN MULTI-STOREY BUILDINGS - Bodnaruk, Oleksii; Bosak, Аlla (General Energy Institute of the National Academy of Sciences of Ukraine, 2025)
In modern conditions, characterized by the destruction of critical infrastructure and instability of energy supply, ensuring a reliable water supply in multi-storey buildings is becoming especially relevant. This article is devoted to the study of the possibilities and problems of using photovoltaic power plants (PV) to power water supply pumps as an alternative energy source. The main goal of the study is to identify key factors that affect the efficiency and reliability of the PV power supply system for water supply pumps, as well as to develop recommendations for their optimization. The influence of weather conditions, in particular solar insolation and air temperature, on the performance of PV plants is analyzed in detail. Seasonal and daily fluctuations in insolation are considered, as well as their dependence on geographical location and atmospheric conditions. The influence of cloudiness, precipitation and fog on the intensity of solar radiation reaching the surface of PV panels is assessed. To analyze the efficiency of the system, a mathematical model has been developed that considers the dependence of the PV output power on solar insolation and panel temperature, the pump power on the required head and volume of water, as well as the operation of the maximum power point tracking (MPPT) algorithm and energy storage. The role of MPPT algorithms in increasing the efficiency of solar energy use is assessed. Ishikawa diagram is used to systematize key constraints. The developed mathematical model allows for a multiple assessment of the impact of various factors on system performance and the development of optimal control strategies.